2010
DOI: 10.1007/s10404-010-0695-z
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-resistant and reversible on-tube-sealing for microfluidics

Abstract: We present the design, manufacturing, and characterization of a novel miniaturized on-tube-seal configuration for microfluidic devices. The seal is based on a previously developed world-to-chip spring-based interface by Kortmann et al. (Lab Chip 9:1455-1460, 2009a, which enables rapid and reliable microfluidic connections. In this study, the dead volumes, the contact pressure, the discontinuous fluidic-profile transmission, and the space requirements were significantly optimized by a new on-tube-seal configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This technique allowed reliable and automatic interconnections to a PMMA chip for pressures as high as 2 MPa. The co-authors of this study later addressed the issue of higher dead volumes typically observed in connections based on O-rings and reduced the dead volume to 18 nL using miniaturized O-rings [183]. More recently, a high-density fluidic connection technique based on flanged PTFE tubings instead of O-rings or gaskets was introduced by Wilhelm et al (Fig.…”
Section: Contact-based Adhesive-free and Reversible Interconnectsmentioning
confidence: 96%
“…This technique allowed reliable and automatic interconnections to a PMMA chip for pressures as high as 2 MPa. The co-authors of this study later addressed the issue of higher dead volumes typically observed in connections based on O-rings and reduced the dead volume to 18 nL using miniaturized O-rings [183]. More recently, a high-density fluidic connection technique based on flanged PTFE tubings instead of O-rings or gaskets was introduced by Wilhelm et al (Fig.…”
Section: Contact-based Adhesive-free and Reversible Interconnectsmentioning
confidence: 96%
“…Outlet (5) offers the possibility to sample secreted metabolites of the isolated and living single bacterium via an on-tube-seal. 26 Finally, inlet (6) and outlet (7) provide the opportunity to rinse the analyzed living bacterium out of the microfluidic chip for cell deposition in cultivation wells and further analyses including growth experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Sampling can be achieved via an on-tube-seal microfluidic connection. 26 In contrast to LOC devices which apply contact trapping for single cell analysis, single cell trapping using the Envirostat 2.0 is less depending on cell nature and allows a microenvironmental controlled isolation and analysis of a broad range of cell types including 0.5-5 mm sized prokaryotes and eukaryotes. In addition to environmental and actively controlled nDEP sorting, isolation and cultivation, the chip allows separation and parallel analysis of daughter cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The open end of the capillary was exposed to a water saturated atmosphere in order to prevent sample evaporation and crystal formation at the capillary tip. A dead volume-reduced microfluidic world-to-chip-interface was used to connect the capillary to the Envirostat chip. , After 12 h of incubation, the capillary, which was filled with the supernatant produced during the preceding 2 h, was removed, sealed with PEEK-MicroTight adapters (P-882, IDEX Health & Science LLC, WA, U.S.A.), and immediately transferred to MS analysis.…”
Section: Methodsmentioning
confidence: 99%